Changing attitudes to punishment: public opinion, crime and justice - Hough, Mike; Roberts, Julian V. (Willan Pub, 2002)
1. Public attitudes to punishment : the context / Julian V. Roberts and Mike Hough -- 2. Measuring attitudes to sentencing / Loretta J. Stalans -- 3. Public opinion and the nature of community penalties : international findings / Julian V. Roberts -- 4. Cross-national attitudes to punishment / Pat Mayhew and John van Kesteren -- 5. The evolution of public attitudes to punishment in western and eastern Europe / Helmut Kury, Joachim Obergfell-Fuchs and Ursula Smartt -- 6. Public and judicial attitudes to punishment in Switzerland / Andre Kuhn -- 7. Public support for correctional rehabilitation in America : change or consistency? / Francis T. Cullen. [and others] -- 8. Attitudes to punishment in the US : punitive and liberal opinions / John Doble -- 9. How malleable are attitudes to crime and punishment? : findings from a British deliberative poll / Mike Hough and Alison Park -- 10. Improving public knowledge about crime and punishment / Catriona Mirrlees-Black -- 11. Strategies for changing public attitudes to punishment / David Indermaur and Mike Hough -- 12. Privileging public attitudes to sentencing? / Rod Morgan.